A total systems study on the distribution operations of Hiyas Marketing - Allapitan, Alexander B.; Barruga, Lorena J.; Corpuz, Janine Cathleen F.; Malimet, Ralph Victor M.
Hiyas Marketing, a distribution company based in Santiago City, lsabela, operates in the provinces of Cagayan, lsabela, Nueva Vizcaya and Quirino. Now on its fourteenth year of prolific business, it plays a vital part in the supply chains of four suppliers- Cosmetique Asia, Renaissance Foods Corporation, Maryland Distributors, Inc., and SC Johnson & Son. The company identifies the lost sales they incur day to day as its foremost source of improvement. Hence, this study aims to identify the root cause of the lost sales and address their occurrences through analysis from a holistic and broad perspective. The Hiyas distribution operations have been documented thoroughly to pinpoint deviations from the desired procedures. It has three main processes, namely purchasing of stocks, warehousing, and order fulfillment of key accounts (large-volume clients) and outlets (small-to-medium-volume clients). The four sources initially credited for the lost sales are the stock outs in the order fulfillment of outlets, bad orders (returned products}, pilferage/non-payment (unlawful external actions}, and truck downtimes. These sources are investigated to zoom in on the main problem to be presented with preventive and mitigating solutions. It is found out that the bad orders, pilferage/non-payment, and truck downtime do not have significant contributions to the lost sales when taken against the impact of stock outs. In 2013, there has been a monthly average of 238 occurrences of stock outs, amounting to approximately PhP 274,000 per month. It is noted that more _stock outs are recorded during the peak months of April, May, and June. A causal chain is primarily illustrated to represent the continuous relay of events that happen before and after the undesired events eventually leading to the stock outs and the dissatisfaction of customers. The causal chain also serves as the basis for the multilayered approach to solution of the identified risk by offering initial proposals. The proposals are evaluated individually through the weighing their advantages and disadvantages and the use of IE tools like forecasting techniques and computation of safety stock. It is noted that coordination with suppliers is necessary to iron out impending stock outs. Better methods of obtaining purchase orders are also needed to accurately record and compute the demand. Obtaining purchase orders is noted as one of the reasons why they are uncertain in the number of stocks to load because current loading is based on intuitive forecasting. It is also recommended to use a Weighted Moving Average or Exponential Smoothing method (depending on the MAD value) in forecasting. The weekly safety stock is also computed per product using historical data. The truck layout is further suggested to prevent misplacing the stocks when distributing them. Finally, a pre-ordering system is suggested to mitigate the risk of stock outs and prevent customer dissatisfaction. Those who order in advance must be given a discount of 15% as incentive.